2003
DOI: 10.1117/1.1578087
|View full text |Cite
|
Sign up to set email alerts
|

Speckle reduction in optical coherence tomography by frequency compounding

Abstract: We are investigating the possibility of a frequency compounding method for speckle reduction in optical coherence tomography. The method is based on incoherent summation of the magnitudes of two independent interferometric signals, which were recorded at two different center wavelengths simultaneously. We derive the corresponding statistics and compare the theoretical results with measurements obtained in a uniformly scattering sample. Finally we demonstrate our method by comparing images of human skin recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(160 citation statements)
references
References 17 publications
(19 reference statements)
2
151
0
Order By: Relevance
“…It has been shown that speckle noise is the most predominant noise source in OCT imaging [3][4][5][6][7][8][9]. Apart from other systemspecific noise like electric or shot noise, speckle is common to all OCT commercial systems [26].…”
Section: Preprocessing For Patch-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that speckle noise is the most predominant noise source in OCT imaging [3][4][5][6][7][8][9]. Apart from other systemspecific noise like electric or shot noise, speckle is common to all OCT commercial systems [26].…”
Section: Preprocessing For Patch-based Methodsmentioning
confidence: 99%
“…In order to quantitatively measure the denoising performance with full reference metrics, synthetic noise OCT images were generated by computationally corrupting virtually noiseless clinical images using a known amount of noise. We obtained images of background noise from a commercial SD-OCT device (i.e., CirrusOCT) in order to characterize the expected noise, which was later employed to computationally alter averaged HD clinical B-scans in a signal-dependent manner (as expected with noise in SD-OCT systems [3][4][5][6][7][8][9]). The effect of corrupting the averaged HD clinical images with a more general simulated speckle noise was also investigated.…”
Section: Experimental Studies To Evaluate Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous speckle reduction methods have therefore been developed and applied to OCT [54]. Some are based on incoherent addition of several signals from the same location under varying conditions, e. g. angular compounding [57], spatial compounding [58,59], and frequency compounding [60]. Where compounding is not feasible different image processing techniques can be applied to suppress speckle, e. g. various types of smoothing filters, deconvolution [61,62], wavelet analysis [63], rotating kernel transformation [64], and anisotropic diffusion [65].…”
Section: Optical Properties Of the Samplementioning
confidence: 99%
“…However speckles provide information about both the structure of the imaged object as well as image noise. Therefore, several approaches have been developed for speckle reduction using angular compounding, [1][2][3][4] frequency compounding, 5 polarization compounding, 6 and strain compounding. 7,8 Angular compounding is performed by averaging multiple images acquired at different angles.…”
mentioning
confidence: 99%